Factors affecting trust in clinical trials conduct: Views of stakeholders from a qualitative study in Ghana - Samuel Tamti Chatio; John Kuumuori Ganle; Philip Baba Adongo; Ulrike Beisel (Public Library of Science (PLoS), 2023)
Evidence exists that scientists' dehumanization and exploitation of people in the name of science led to suspicion and mistrust in clinical trials conduct. In Ghana, there are equally signs of public distrust in the conduct of biomedical research. Typical examples are the unsuccessful conduct of the Ebola vaccine trial and the initial refusal of parents to allow their children to receive the recently piloted malaria vaccine in Ghana. Therefore, this study explored participants' views on factors affecting trust in clinical trials conduct in Ghana. This was a cross-sectional exploratory study using qualitative research approach. Forty-eight in-depth interviews and Key informant interviews were conducted with stakeholders. Purposive sampling technique was used to select participants. All the interviews were recorded, transcribed and coded into themes using QSR Nvivo 12 software to aid thematic analysis. Overall, participants saw the need for the conduct of clinical trials in Ghana because clinical trial studies enable scientists to come out with effective medicines for the management of diseases. Pre-implementation factors such as inadequate stakeholder engagement, rumours and negative influence affected trust. Implementation factors such as perceived risks about clinical trials medicines, apprehensions on drawing and use of blood samples, poor informed consent administration and perceived no illness all negatively affected trust in clinical trials conduct. Trust is a fundamental factor affecting a successful conduct of clinical trials. Thus, there is need for collective efforts by all stakeholders including research institutions and clinical trial regulatory bodies to take the issue of trust in clinical trials conduct seriously.